FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Felicia Karlinda; Ferry Suhardjo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study was conducted to determine the effect of firm size, profitability, solvability, size of the public accounting, firm age, board size, and leverage on audit report lag in manufacturing companies in Indonesia. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange during the period 2018 to 2020. The sample of this research are selected with using purposive sampling method, and 234 datas are taken. Data were analyzed using multiple regression method. The results showed that size of the public accounting has influence to audit report lag. While firm size, profitability, solvability, firm age, board size, and leverage have no effect to audit report lag.